ERGONYMS AS AN ELEMENT OF THE ONOMASTIC STRUCTURE OF THE MODERN RUSSIAN LANGUAGE - Asanova A.; Abdumanapova Z. Z. (Vestnik Issyk-Kulʹskogo universiteta)
In this article, the relevance of studying ergonyms in contemporary Russian is discussed. This relevance is due to their significant role in reflecting the socio-economic and cultural changes in society. Ergonyms, as proper names of commercial organizations, are an important object of analysis because they demonstrate the language's adaptation to globalization and economic trends. The author notes that studying ergonyms reveals features of language play and a creative approach to naming, which contribute to shaping cultural identity and the image of the urban environment. In the context of increased borrowing and integration of foreign elements, ergonyms become an expression of global changes, necessitating linguistic analysis of their word-formation and semantic characteristics. The study of these proper names deepens the understanding of onomastic structures in the Russian language, contributes to expanding knowledge of the interdisciplinary connections between linguistics and sociology, and helps to realize the role of cognitive processes in naming objects. Thus, the study of ergonyms is a significant contribution to understanding the dynamics of language change and cultural transformations in the modern world.